Shooting Accuracy And Leg Muscle Strength In Relation To The Goal Of The Palu Putra Fc Football Team - Usbah, Muh; Agusman, Muhammad; Sianto, Moh. Ifkhal; D. Kandupi, Ardiansyah; Zainuddin, Erwin (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective . The purpose of this study was to determine the relationship between leg muscle strength and shooting accuracy towards the goal of Palu Putra FC players. Material and Methods. Research method is a way used by researchers in collecting research data (Arikunto: 2010). The method used in this study is a descriptive correlational method, namely the Pearson Product Moment Correlation method. The sample is a part or representative of the population to be studied (Arikunto: 2010). The sample of this study is the entire population of 20 participants so that this study is called population research. Results. The results of this study indicate that In other words, there is a significant relationship between leg muscle strength and shooting accuracy towards the goal in extracurricular students of SMP Patra Mandiri 2 Palembang, marked by the results obtained, namely t count 11.47> t table 1.714 with a contribution of 88% and 12% influenced by other factors. Conclusion. Based on the results of the research and discussion that have been presented in the previous description, it can be concluded that there is a significant relationship between the independent variables and the dependent variables. In other words, there is a significant relationship between leg muscle strength and shooting accuracy towards the goal at Palu Putra FC, marked by the results obtained, namely t count 11.47> t table 1.714 with a contribution of 88% and 12% influenced by other factors. This shows that the better the leg muscle strength of Palu Putra FC, the better the shooting ability towards the goal they have.